Less Is More?-A Feasibility Study of Fluid Strategy in Critically Ill Children With Acute Respiratory Tract Infection - Sarah A. Ingelse; Vincent G. Geukers; Monique E. Dijsselhof; Joris Lemson; Reinout A. Bem; Job B. van Woensel (Frontiers Media S.A., 2019)
Background: Fluid overload is common in critically ill children and is associated with adverse outcome. Therefore, restricting fluid intake may be beneficial. This study aims to study the feasibility of a randomized controlled trial (RCT) comparing a conservative to a standard, more liberal, strategy of fluid management in mechanically ventilated pediatric patients with acute respiratory tract infection (ARTI).Methods: This is a feasibility study in a single, tertiary referral pediatric intensive care unit (PICU). Twenty-three children receiving mechanical ventilation for ARTI, without ongoing hemodynamic support, admitted to the PICU of the Emma Children's Hospital/Amsterdam UMC between 2016 and 2018 were included. Patients were randomized to a conservative (<70% of normal intake) or standard (>85% of normal intake) fluid strategy, which was kept throughout the period of mechanical ventilation.Results: Primary endpoints were adherence to fluid strategy and safety parameters such as calorie and protein intake. Secondary outcomes were cumulative fluid intake (CFI) and cumulative fluid balance (CFB) on day 3. In the conservative group, in 75% of the mechanical ventilation days patients achieved their target fluid intake. Median [25th−75th percentiles] calorie intake over all mechanical ventilation days was 67.9 [51.5-74.0] kcal/kg/day in the conservative vs. 67.2 [58.0-75.2] kcal/kg/day in the standard group (p = 0.878). Protein intake was 1.6 [1.3-1.8] gr protein/kg in the conservative and 1.5 [1.2-1.7] gr protein/kg in the standard group (p = 0.598). No adverse effects on hemodynamics or electrolyte imbalances were noted. Mean (±SD) CFI on day 3 was 262.3 (±58.9) ml/kg in the conservative group vs. 360.5 (±52.6) ml/kg in the standard fluid group (p < 0.001), which did not result in a lower CFB.Conclusions: A conservative fluid strategy in mechanically ventilated children with ARTI seems feasible, without limiting metabolic needs. However, in our study a conservative fluid strategy surprisingly did not reduce the degree of fluid overload. This study aids the design and sample size calculation of a future larger multicenter RCT, in which we need to redefine the target fluid strategy, possibly by even further fluid restriction and early initiation of active diuresis.Clinical Trial Registration: ClinicalTrials.gov, identifier: NCT02989051.